A fast response and red emission probe for mammalian thioredoxin reductase. Issue 81 (19th September 2016) - Ma, Huilong; Zhang, Junmin; Zhang, Zhenzhe; Liu, Yaping; Fang, Jianguo
Abstract : The first red emission probe, TRFS-red, for thioredoxin reductase was reported with improved response rate and sensitivity. Abstract : The first red emission off–on probe, TRFS-red, for thioredoxin reductase was reported. Compared to the previous green emission probe TRFS-green, TRFS-red maintains a high selectivity to the redox enzyme yet with improved response rate and sensitivity.